The emergence of autobiography in Malay literature - Hamdan, Rahimah; Sujud, Arba'ie; Md Radzi, Shaiful Bahri (Medwell Journals, 2016)
This study aims to compare and analyse the arguments of several scholars with regard to the classification and significance of autobiographies and biographies in Malay historiography. Western colonialism, especially by the English and Dutch who came to the Malay world in the 17th and 18th centuries, introduced a new trend that expanded rapidly in line with the Industrial Revolution in Europe, namely a trend of realism in literature. This trend obviously emphasized the manifestation of “reality” without mixing it up with “supernatural” elements to form a new genre known as autobiographies and biographies in conventional Malay literature. Abdullah Munshi’s crowning work titled Kisah Pelayaran Abdullah which was considered as the earliest autobiography to be written in the Malay language, invited debate from several scholars that extended to a number of other autobiographical and biographical texts that emerged in the late 19th century and early 20th century. Local and Western scholars such as Syed Naquib al-Attas, Liaw Yock Fang, C.W. Watson and A. Sweeney tried to explain their own scale and classification of the terminology and interpretation of this genre to suit the values and thinking in conventional Malay literature. Hence, through the use of qualitative methods this study will discuss the opinions of the above scholars and at the end of this study will present a scale of the autobiographies and biographies genre that coincides with the Malay perspective.